Influence of gamma radiation and EMS on chlorophyll and macro-mutation in mungbean (Vigna radiata) - KUMAR, RAVINDER; SHARMA, N K (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried during rainy (kharif) season of 2021 (M1 generation), summer 2022 (M2 generation) and rainy (kharif) seasons of 2022 (M3 generation) at College of Agriculture, Swami Keshwanand Rajasthan Agricultural University, Bikaner, Rajasthan for creating genetic variability in mungbean [Vigna radiata (L.) R. Wilczek]. The experiment was conducted with 26 treatments and 2 popular archaic varieties of mungbean (Ganga-1 and GM-4), solitary application of gamma radiation (200, 400 and 600 Gy), and ethyl methane sulphonate (EMS) (0.1 and 0.2%) as well as their combinations. A wide spectrum of chlorophyll mutants (Chlorina, Xantha, Albina, Viridis and complex type) and morphological mutants (plant type, flower colour, pod type, leaf variation and maturity period) were identified at various crop growth stages. All mutagen treatments including solitary application of gamma radiation and EMS as well as their combinations were found effective for creating genetic variability. The lower concentration of EMS (0.1%) was found to be relatively more effective as compared to 0.2%. Similarly, the lower dose of gamma radiation (200 Gy) was also more effective than 400 and 600 Gy. Among all the treatment combinations, combined application of 200 Gy + 0.1% EMS was found most effective in generating chlorophyll and morphological mutants. Among two varieties of mungbean, Ganga-1 was found to be more sensitive to mutagens as compared to GM-4. Numerous mutants identified in the mutagenized population of both varieties exhibited stability and superiority in terms of agro- morphological traits over Ganga-1 and GM-4. A mutant (S-92 of GM-4) identified during M1 in mutagen treatment 0.1% EMS was very deep lobbed which altered the plant morphology and appearance. This novel unique mutant identified in M1 generation maintained its stability in M2 and M3 generations also. The leaf colour of this mutant was darker than the original leaf colour of GM-4 and found relatively more tolerant to soil moisture-deficit stress.